ظاهرة التدخل الخارجي بين الشرعية والنزاعات الدولية - حيدر, عفيف; اسماعيل, عصام; ميليش, فريد (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The phenomenon of external interference is one of the most controversial phenomena in international relations. In many cases, it has been a cause or a result of international conflicts, especially since changes in the international system have imposed major changes on this phenomenon. This contradicts the principles of sovereignty and non- Which was adopted by the international conventions. The international standards were used by the international system to achieve its objectives, exploiting political and humanitarian issues and issues that justify the intervention of states and the use of force for hegemony through political and humanitarian justification for its colonial project. What has led to an increase in the phenomenon of external interference, the use of violence and force directly, which is a violation of the national sovereignty of the State. إن ظاهرة التدخل الخارجي من أكثر الظواهر تعرضاً للجدل في العلاقات الدولية، وكانت في الكثير من الأحوال سبباً, أو نتيجةً للنزاعات الدولية لاسيما أن التغيرات في النظام الدولي فرضت تحولات كبرى على تلك الظاهرة, مما يتعارض مع مبدأي السيادة وعدم التدخل في شؤون الدول، اللذين أقرتهما المواثيق الدولية, فسادت صيغ الكيل بمكيالين في القضايا الدولية, واستخدمها النظام العالمي لتمرير أهدافه, مستغلاً مسائل وقضايا سياسية, وانسانية تبرر تدخل الدول واستخدام القوة للهيمنة عبر وضع مبررات سياسية وأنسانية لمشروعها الاستعماري, واتسع ذلك مع ظهور الإرهاب وانتشاره ما أدى بشكلٍ ما إلى ازدياد ظاهرة التدخل الخارجي, وهو استخدام للعنف والقوة بشكل مباشر , أي هو انتهاك للسيادة الوطنية للدولة.